2014
DOI: 10.1136/bjophthalmol-2013-304019
|View full text |Cite
|
Sign up to set email alerts
|

Different effects of intravitreally injected ranibizumab and aflibercept on retinal and choroidal tissues of monkey eyes

Abstract: Ranibizumab permeated the retina through intercellular spaces, whereas aflibercept was taken up by neuronal and RPE cells. Aflibercept induced protein complex formation and more haemolysis in the choriocapillaris, leading to individual RPE cell death. The clinical significance and relation of these findings to the Fc domain or to other characteristics of aflibercept remain to be investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
56
1
3

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(63 citation statements)
references
References 40 publications
3
56
1
3
Order By: Relevance
“…It has been reported that VEGF inhibition can activate thrombocytes in humans treated for cancer [28] or for neovascular AMD [18]. In addition, VEGF inhibition after intravitreal application induced thrombotic microangiopathy in the choriocapillaris of monkeys [29][30][31][32]. In the present study, evidence for thrombotic occlusion of neovascular vessels after VEGF inhibition is shown (Fig.…”
Section: Discussionsupporting
confidence: 68%
“…It has been reported that VEGF inhibition can activate thrombocytes in humans treated for cancer [28] or for neovascular AMD [18]. In addition, VEGF inhibition after intravitreal application induced thrombotic microangiopathy in the choriocapillaris of monkeys [29][30][31][32]. In the present study, evidence for thrombotic occlusion of neovascular vessels after VEGF inhibition is shown (Fig.…”
Section: Discussionsupporting
confidence: 68%
“…25 Aflibercept reduced the thickness and number of fenestrations of the choriocapillaris in monkey eyes more profoundly than ranibizumab, possibly by an interaction between an Fc fragment and other molecules. 26 This property, which might be both beneficial and unfavorable, may explain the effect of aflibercept on CT and PED in the present study. Considering the association between CVH and CT, reduction in CT may indicate suppression of CVH after aflibercept treatments, though we did not evaluate the status of CVH after treatments.…”
Section: Discussionmentioning
confidence: 57%
“…Although unknown, this might depend on the pathway of anti-VEGF action; if PED flattening is related to a reduced exudative activity of the neovascular mass, the flattening might represent a healthier situation for the pigment epithelium. However, if there is some toxicity to the retinal pigment epithelium, which has been suggested by some animal and in vitro studies, 32,33 this flattening might rather be related to retinal pigmented epithelium damage and reduced pump function. Our short-term functional results showed good BCVA improvement regardless of the drug type used.…”
Section: Discussionmentioning
confidence: 95%